2011
DOI: 10.1124/jpet.110.178343
|View full text |Cite
|
Sign up to set email alerts
|

NaVβ Subunits Modulate the Inhibition of NaV1.8 by the Analgesic Gating Modifier μO-Conotoxin MrVIB

Abstract: Voltage-gated sodium channels (VGSCs) consist of a pore-forming ␣-subunit and regulatory ␤-subunits. Several families of neuroactive peptides of Conus snails target VGSCs, including Oconotoxins and -conotoxins. Unlike -conotoxins and the guanidinium alkaloid saxitoxin (STX), which are pore blockers, O-conotoxins MrVIA and MrVIB inhibit VGSCs by modifying channel gating. O-MrVIA/B can block Na V 1.8 (a tetrodotoxinresistant isoform of VGSCs) and have analgesic properties. The effect of Na V ␤-subunit coexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
(50 reference statements)
4
46
0
Order By: Relevance
“…Indeed, voltage-dependent relief of Na v 1.4 inhibition by MrVIB was attributed to the voltage sensor of domain II (Leipold et al, 2007), another site shared with ␤ scorpion toxins. Similar effects were also reported for Na v 1.8, where the K off of MrVIB was also accelerated by strong depolarizations (Wilson et al, 2011b). However, compared with Na v 1.4, the K off of MrVIB at Na v 1.8 was significantly slower and required repeated depolarizations to relieve block (Wilson et al, 2011b).…”
Section: B O-conotoxin Inhibitors Of Voltage-gated Sodium Channelssupporting
confidence: 57%
See 3 more Smart Citations
“…Indeed, voltage-dependent relief of Na v 1.4 inhibition by MrVIB was attributed to the voltage sensor of domain II (Leipold et al, 2007), another site shared with ␤ scorpion toxins. Similar effects were also reported for Na v 1.8, where the K off of MrVIB was also accelerated by strong depolarizations (Wilson et al, 2011b). However, compared with Na v 1.4, the K off of MrVIB at Na v 1.8 was significantly slower and required repeated depolarizations to relieve block (Wilson et al, 2011b).…”
Section: B O-conotoxin Inhibitors Of Voltage-gated Sodium Channelssupporting
confidence: 57%
“…Similar effects were also reported for Na v 1.8, where the K off of MrVIB was also accelerated by strong depolarizations (Wilson et al, 2011b). However, compared with Na v 1.4, the K off of MrVIB at Na v 1.8 was significantly slower and required repeated depolarizations to relieve block (Wilson et al, 2011b).…”
Section: B O-conotoxin Inhibitors Of Voltage-gated Sodium Channelssupporting
confidence: 57%
See 2 more Smart Citations
“…These results suggest that the auxiliary subunits are functionally conserved among different insect species. A recent study has shown that that the channel affinity of the conotoxin MrVIB, a mammalian sodium channel blocker isolated from the cone snail Conus marmoreus, is strongly influenced by the co expression of -subunits (Wilson et al, 2011). Their high conservation among different insect species, their wide expression in distinct tissues together with the observation that they are involved in the neurotoxin-channel interaction raises the intriguing question whether the insect auxiliary subunits might represent interesting new phyla-selective targets for neurotoxin insecticides.…”
Section: Structural Comparison Between Mammalian and Insect Na V Chanmentioning
confidence: 99%